Skin Mucus of Marine Fish as a Source for the Development of Antimicrobial Agents - Tiralongo, Francesco; Messina, Giuseppina; Lombardo, Bianca Maria; Longhitano, Lucia; Li Volti, Giovanni; Tibullo, Daniele (Frontiers in Marine Science, 2020)
Fish skin mucus is an important component of innate immune mechanism and provides a first barrier against pathogens. Although several studies investigated and demonstrated the antimicrobial properties of skin mucus of fishes, most of them tested antimicrobial properties against marine microbial strains as potential use in aquaculture. Furthermore, most of these studies concerned freshwater species, and far less attention was given to skin mucus of marine fishes for potential application in human health and research towards its antimicrobial properties. This review outines the importance of marine fishes as an important and effective source of antimicrobial drugs against several human pathogens thus providing an highly available and low cost tool to counteract clinical infections.